Process optimization of dried green mangoes (Magnifera indica linn. Carabao) using osmotic dehydration and high temperature drying - Paclibar, Paula Melissa Gomez (College of Home Economics, University of the Philippines Diliman, 2012)
This study aimed to determine the optimum process conditions for the production of dried green mangoes (Magnifera indica Linn. Carabao) using high temperature drying and osmotic dehydration. Response Surface Methodology was used to determine the effect of salt concentration, soaking time, and drying temperature on water activity, color, consumer acceptability, color, texture, saltiness, and green mango flavor. The results for optimization were also compared with the results of the microbiological quality analysis and sensory analysis. Samples soaked in low salt concentrations (10%) have shorter drying times than those soaked in high salt concentrations (20%). Also, samples soaked for longer periods of time (9 hours) have shorter drying times provided that they are soaked in low salt concentrations. Soaking time had a significant effect (p<0.05) on the sensorial attributes of the product. The combination of the three parameters (salt concentration, soaking time, drying temperature) also affected the sensory and microbiological quality of samples. High temperatures had a negative effect on the acceptability of color and texture. High solute concentration and longer soaking times increase solute uptake thereby preventing microbial growth. Numerical and graphical optimization show that the optimum process requirements are 10% salt solution, 6 hours soaking time, and 75°C drying temperature.